10(6x+11)=

Simple and best practice solution for 10(6x+11)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10(6x+11)= equation:


Simplifying
10(6x + 11) = 0

Reorder the terms:
10(11 + 6x) = 0
(11 * 10 + 6x * 10) = 0
(110 + 60x) = 0

Solving
110 + 60x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-110' to each side of the equation.
110 + -110 + 60x = 0 + -110

Combine like terms: 110 + -110 = 0
0 + 60x = 0 + -110
60x = 0 + -110

Combine like terms: 0 + -110 = -110
60x = -110

Divide each side by '60'.
x = -1.833333333

Simplifying
x = -1.833333333

See similar equations:

| 6x+6=4(2x+1) | | 4lnx=20 | | -10x-11+12x-15=-4 | | 4-(3x+6)=-10 | | 5(x-8)=-11 | | b/13-9b/13=40/13 | | 12x-4=24x+4 | | (-2)+2(12)=a | | -10x-11+12x-15=4 | | 3y+4-y=10+y | | 3.2g+6=6+3.2g | | -4x-2(3x-7)=-6 | | 22a-2a+43.465=3a | | 3y-1+4y=8-9+7y | | 4=4(1-4x)+8(x-4) | | 3[-4-(-4+5)]= | | 3(y-8)=-y | | 7x(6x-2)=180 | | 4x=3y-7-2x | | 16y-8-8y=27 | | 10.2a+3.9=32a | | -5+h=-34 | | -4m(-7n)+(3d)(-4c)= | | 5x^2+3x-6=0 | | 4088=x(56) | | .5+.4= | | 8x+2(12x+6)= | | x+(2x-30)=150 | | 5-(5.25+3.1x)=-6.2(2.5x+1.9) | | 5(y-1)=13-y | | 2m^2-9m-35=0 | | 6(x+5)=-36 |

Equations solver categories